2015
DOI: 10.1080/08873631.2014.995403
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant businesses, place-making, and community development: a case from an emerging immigrant gateway

Abstract: Immigrant businesses have become an increasingly important component in the US economy. However, very few studies have systematically examined the role of immigrant businesses in community development, except for some cases in established immigrant gateways such as New York and Miami. In this study, we explore how immigrant businesses are shaping physical, cultural, social, economic, and political landscapes in their local communities in the emerging immigrant gateway of Charlotte, North Carolina. Focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…At present, many newly arrived immigrants usually head to this place for jobs and rental houses where they can also build up their friend network and accumulate their social capital. In a word, this case study more or less proved the presumption that the ethnic economy positively influences the economic integration of immigrants [9].…”
Section: Active Economic Integration: Informality Social and Human Cmentioning
confidence: 53%
See 2 more Smart Citations
“…At present, many newly arrived immigrants usually head to this place for jobs and rental houses where they can also build up their friend network and accumulate their social capital. In a word, this case study more or less proved the presumption that the ethnic economy positively influences the economic integration of immigrants [9].…”
Section: Active Economic Integration: Informality Social and Human Cmentioning
confidence: 53%
“…Traditional studies perceive immigrants as passive actors in the economic integration process [7,8]. However, recently, more studies have shown that immigrants are playing a much more active role (e.g., informality, human and social capital accumulation, ethnic economy), which presents a transformation from passive economic integration to active economic integration [9,10]. However, this transformation is disputed as immigrants' more active economically integrating behavior does not represent a positively successful economic integration [11].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic entrepreneurs are key players in the ethnic placemaking process. Schuch and Wang () focused on the Central Avenue ethnic business corridor of Charlotte, North Carolina, and argued that placemaking entails the active engagement of people in the places they inhabit. They described ethnic placemaking practices as having ‘multiple interrelated dimensions (physical, cultural, social, economic, and political) and an ever‐changing two‐way interactive process between immigrant businesses and their communities’ (Schuch & Wang , p. 218).…”
Section: Placemaking Through Ethnic Entrepreneurshipmentioning
confidence: 99%
“…Ethnic businesses, as one of the most visible markers of immigrant settlement and multiculturalism, are undoubtedly embedded in ‘places’, which, in contrast to physical ‘spaces’ are understood as ‘the geographical context for the mediation of physical, social and economic processes’ (Agnew , p. 317). Although little research has examined the intersection between place and ethnic entrepreneurship, a few studies have used social/cultural, economic, physical, and political lenses to observe ethnic businesses and explore placemaking processes (Wood ; Wang ; Liu et al ; Schuch & Wang ; Zhuang ; Zhuang & Chen ). Ethnic placemaking is generally discussed within an urban context, as suburbs are often characterised as ‘placeless’.…”
Section: Introductionmentioning
confidence: 99%